Public Relations Planning In Building A Private University Branding During The Covid-19 Pandemic (A Case Study at Universitas Swadaya Gunung Jati Cirebon) - Iman Cahyanto; Iim Wasliman; Fahruroji; Supyan Sauri (CV. AFDIFAL MAJU BERKAH, 2022)
This research is focused on investigating the public relations planning in building a private university branding during the COVID-19 pandemic. University branding is a strategic effort in strengthening the identity of the institution. In practice, branding can be done in various ways, such as by utilizing information technology. During the COVID-19 pandemic, the frequency of using internet-based media increased dramatically. The phenomenon that occurs in public relations during a pandemic is the changing pattern of media publications, from conventional media and internet-based media to internet-based media. The phenomenon changed the public relations management structure in building university branding and the lack of maximum branding achievements that have been set in the previous program before the pandemic. The concept of public relations management in universities establishes theoretical principles in formulating and implementing public relations management to build university branding. Referring to the management theory of George R. Terry who stated that the management is carried out based on the main points of the formulation of organizational goals (Riinawati, 2019). The implementation of university branding in the current pandemic situation and conditions must not be outside the corridor of management functions. This study aimed to find out how to plan university branding during the pandemic. Based on the results of the research on public relations planning in building the branding of private universities during the pandemic, the implementation process of public relations management planning has not been formulated in a standardized manner so that it cannot improve public relations performance during a pandemic in a timely manner. This has an impact on achievement that is not optimal. In order for the university's public relations performance to increase and the implementation of university public relations management to improve the brand, and provide the expected feedback, the university's public relations planner needs to reformulate the university's public relations management structure. The right formulation of the results of this research is a planning model that involves information technology as a domain of digitization in public relations management. The current technology involvement is expected to improve the university's branding performance during the pandemic. More specifically, public relations management planning in building private university branding during the pandemic needs to develop systematic and strategic steps that refer to the rules of planning function in public relations management to be able to improve the university branding process. The preparation of the branding plan in the form of an activity program does not include: creative content adapted to current conditions, human resource development planning and public relations support facilities such as training on the use of information technology for public relations staff. Procurement of computer equipment, property for making videos and making information technology studios.